Zooming in on the circumgalactic medium with GIBLE: the topology and draping of magnetic fields around cold clouds : letter to the editor - Ramesh, Rahul; Nelson, Dylan; Fielding, Drummond; Brüggen, Marcus (Astronomy and astrophysics, 2024)
We used a cosmological zoom-in simulation of a Milky Way-like galaxy to study and quantify the topology of magnetic field lines around cold gas clouds in the circumgalactic medium (CGM). This simulation is a new addition to Project GIBLE, a suite of cosmological magnetohydrodynamic simulations of galaxy formation with preferential super-Lagrangian refinement in the CGM, reaching an unprecedented CGM gas mass resolution of ∼225 M⊙. To maximize statistics and resolution, we focused on a sample of ∼200 clouds with masses of ∼106 M⊙. The topology of magnetic field lines around clouds is diverse, from threading to draping, and there is large variation in the magnetic curvature (κ) within cloud-background interfaces. We typically find little variation of κ between upstream and downstream cloud faces, implying that strongly draped configurations are rare. In addition, κ correlates strongly with multiple properties of the interface and the ambient background, including cloud overdensity and relative velocity, suggesting that cloud properties impact the topology of interface magnetic fields.